The Influence of Tafakur Alam Activities on Students' Critical Thinking Skills in PAI Subjects at SMP Baitul Arqam Qur'anic Science Sumedang - Supala, Supala; Sundari, Susan; Dalianidurisa, Niken Ankapristya (Pendidikan Agama Islam STIT Palapa Nusantara, 2024)
The implementation of natural tafakur activities in schools still cannot be optimized when followed by students because students do not understand the concept of natural tafakur, and cannot develop their thinking skills more deeply (critically). The formulation of the problem from this study is; (1) How are the nature tafakur activities at SMP Baitul Arqam Qur‟anic Science Sumedang? (2) How is the critical thinking ability of students in PAI subjects at SMP Baitul Arqam Qur‟anic Science Sumedang? and (3) How does the influence of natural tafakur activities on students' critical thinking skills in PAI subjects at SMP Baitul Arqam Qur‟anic Science Sumedang? The research method used is quantitative descriptive which is correlational. Data collection techniques are observation, questionnaires, and literature studies. Quantitative data analysis of this study using SPSS Version 25 application. Based on the results of data analysis, there are the following results; Tafakur Alam activities at SMP Baitul Arqam Qur‟anic Science Sumedang obtained a percentage result of 88.6% in the very good category. Critical Thinking Skills Students at SMP Baitul Arqam Qur‟anic Science Sumedang obtained a percentage result of 81% in the very good category. The influence of natural tafakur activities on students' critical thinking skills has a correlation value of 0.739 with a high category. Data analysis of the sign of regression coefficient (b) with a positive sign (B = 739), natural tafakur activities with students' critical thinking skills have a unidirectional relationship. The closeness of the relationship r=0.671 with the High category. Have a significant relationship (sig = 0.000). R Square = 0.450 with medium category, nature tafakur activities contribute to the critical thinking skills of students of SMP Baitul Arqam Qur‟anic Science Sumedang by 45%. The benefits of research are; can make students more enthusiastic in living the nature tafakur, can be used as a source of reference / additional reference related to the concept of nature tafakur and critical thinking, and can be used as a positive contribution material to improve the quality of schools.